Analysis of Scientific Knowledge Requirements from the Perspective of Philosophy of Science in the Digital Age - Sausan, Mona Alyaa; Hasanah, Laila Rahmi; M. Sirozi, M. Sirozi (Journal of Educational Sciences, 2025)
Scientific knowledge in higher education increasingly faces challenges in the digital age where information proliferation and technological transformation threaten scientific integrity. This systematic literature review examined philosophical requirements of scientific knowledge from ontological, epistemological, and axiological perspectives. Using purposive sampling across SCOPUS and Web of Science databases, 45 peer-reviewed studies published 2020-2025 were analyzed through qualitative content analysis with hermeneutic interpretation guided by PRISMA 2020 guidelines and assessed using AMSTAR 2 checklist. Findings revealed that scientific knowledge requires ontological clarity regarding nature and structure, epistemological rigor through empirical and systematic processes, and axiological grounding in ethical values. Institutions implementing comprehensive frameworks integrating these three philosophical dimensions across teaching, research, and community engagement demonstrated 15-20 percent improvements in student engagement and academic performance. The study concludes that explicit philosophical integration is essential for maintaining institutional credibility and societal relevance. However, significant implementation gaps persist between institutional mission statements and operational practices across higher education institutions worldwide.